Preschool children and excess weight: the impact of a low complexity intervention in public day care centers - Nascimento, Viviane Gabriela; Silva, Janaína Paula Costa da; Machado, Thais Costa; Bertoli, Ciro João; Valenti, Vitor Engrácia [UNESP]; Leone, Claudio (My University, 2013)
Introduction: childhood obesity is a major public health problem, affecting children even at early ages. Objective: to assess the impact of dietary intervention and relatively simple physical activity on the nutritional state of preschoolers. Method: this was an intervention study in public daycare centers targeting children from 2 to 4 years of age, in the State of São Paulo. The sample consisted of 9 daycare centers covering 578 children, with 264 children in the intervention group (IG) and 314 in the comparison group (CG). Intervention was focused on modifications in diet and physical activity, avoiding overloading the routine of daycare centers, for duration of one year. A zBMI score > 1 (zBMI) and < 2 was considered risk of being overweight, and > 2 zBMI was considered excess weight (overweight and obese). Analysis was done by frequency calculations, comparisons of proportions by χ2, mean comparisons by t-student and calculations according to Pearson’s correlation coefficient. Results: IG showed an inverse correlation between the initial zBMI of the children and the difference with the zBMI at the end of the intervention (rP = -0.39, p <0.0001). The mean difference of zBMI of the overweight children in IG between the beginning and the end of the study period was negative (-0.46 z score), indicating weight reduction, while the children in the CG was positive (+0. 17 z score) (p = 0.0037). Conclusion: intervention in diet and physical activity in overweight preschool children in daycare centers could have a favorable impact on the evolution of their nutritional state.

Introdução: obesidade infantil é importante problema de saúde pública, afetando inclusive crianças muito precocemente. Objetivo: avaliar o impacto de uma intervenção alimentar e de atividade física relativamente simples no estado nutricional de pré-escolares. Método: estudo de intervenção em creches públicas visando as crianças de 2 a 4 anos incompletos de idade, no Estado de São Paulo. A amostra foi de 9 creches abarcando 578 crianças, sendo 264 crianças no grupo intervenção (GI) e 314 no grupo comparação (GC). A intervenção foi voltada para modificações na alimentação e na atividade física, evitando sobrecarregar a rotina das creches, com duração de um ano. Considerouse um escore z de IMC > 1 (zIMC) e < 2 como risco de sobrepeso, e zIMC > 2 como excesso de peso(sobrepeso e obesidade). A análise foi por cálculos de frequências, comparações de proporções pelo χ2, comparações de médias pelo t de Student e cálculo dos coeficientes de correlação de Pearson. Resultados: o GI mostrou correlação inversa entre o zIMC inicial das crianças e a diferença deste com o zIMC ao final da intervenção (rP= -0,39; p<0,0001). A média das diferenças do zIMC das crianças com excesso de peso do GI entre o início e o final do período de estudo foi negativa (-0,46 escore z), indicando redução de peso, enquanto nas crianças do GC foi positiva (+0,17 escore z), (p = 0,0037). Conclusão: intervenção na alimentação e nas atividades físicas de pré-escolares com excesso de peso em creches pode ter impacto favorável na evolução de seu estado nutricional.
Pré-escolares e excesso de peso: impacto de uma intervenção de baixa complexidade em creches públicas